Sustainable belt conveyor operation by active speed control. (15th March 2020) - He, Daijie; Liu, Xiangwei; Zhong, Bin
Graphical abstract: Highlights: Estimation-Calculation-Optimization method applicable to consider conveyor dynamics. The Delft Systems Approach applicable to model speed-controlled belt conveyor system. A control algorithm takes time-overlapping conflicts into account for speed control. Considerable energy saving can be achieved by applying active speed control. Abstract: Belt conveyor systems play an important role in dry bulk material handling. Speed control is a promising solution to improve energy efficiency of belt conveyors. Active speed control algorithm was proposed for application on individual belt conveyor. This work investigates its application on a multi-belt conveyor system. The Delft Systems Approach is used to model both operation and control systems. The dynamic behaviour of conveyor belts during transient state is taken into consideration. A Simulation study of a dual-belt conveyor system is carried out to verify the proposed active speed control algorithm. Simulation results show that during eight hours' operation, active speed control can achieve hourly average energy saving of 16.21% compared with constant speed operation scenario. The simulation study verifies that active speed control on belt conveyor systems leads to more sustainable operation.